A total EQD2 greater than 85 Gy for trachea and main bronchus D2cc being associated with severe late complications after definitive endobronchial brachytherapy - Murakami, Naoya; Kobayashi, Kazuma; Nakamura, Satoshi; Wakita, Akihisa; Okamoto, Hiroyuki; Tsuchida, Keisuke; Kashihara, Tairo; Harada, Ken; Yamada, Mayuka; Sekii, Shuhei; Takahashi, Kana; Umezawa, Rei; et al. (Journal of Contemporary Brachytherapy, 2015)
Purpose : The endobronchial brachytherapy (EBBT) is an established treatment method for tumors of the tracheobronchial system, however, little is known about the tolerance dose for organ at risk (OAR) in EBBT. The purpose of this study is to analyze patients with superficial bronchial carcinoma treated with definitive EBBT, and to investigate a relationship between late complications and dose for OAR. Material and methods : Endobronchial brachytherapy was performed 6 Gy per fraction for three to four fractions with or without external beam radiation therapy (EBRT). For the purpose of dosimetric analysis, the wall of the lower respiratory tract (LRT: trachea, main bronchus, and lobar bronchiole), trachea, and main bronchus (TMB) was extracted. D 0.5cc , D 1cc , and D 2cc of LRT and TMB were calculated in each EBBT session and added together. V 100 , V 150 , and V 200 of LRT were also calculated. Results: Between March 2008 and April 2014, EBBT was performed in 14 patients for curative intent. The 2-year overall survival (OS), progression-free survival (PFS), and local recurrence free survival (LRFS) was 82.1%, 77.9%, and 91.7%, respectively. There was one patient with grade 5, one grade 4, and three grade 3 obstruction of trachea or bronchus. The mean EQD 2 of LRT D 2cc , TMB D 2cc , D 1cc , and D 0.5cc of patients with or without late severe respiratory complications was significantly different between two groups (p = 0.018, 0.008, 0.009, and 0.013, respectively). The 2-year incidence rates of late severe complications in patients with TMB D 2cc ≤ 85 Gy in EQD 2 and > 85 Gy were 0% and 83.3%, respectively with a statistically significance (p = 0.014). Conclusions : It was discovered that TMB D 2cc > 85 Gy in EQD 2 is a strong risk factor for severe late respiratory complication after EBBT.